Evaluation of Critical Static Loads of Three-Layered Annular Plate with Damaged Composite Facings - PAWLUS, Dorota (Engineering Transactions, 2016)
This paper presents the approach to evaluate the critical, static loads of three-layered annular plate with composite facings whose laminas are damaged. The plate is composed of thin, laminated fibre-reinforced composite facings and a thicker, foam core. The fibre and matrix cracks of facing laminas influence the plate critical state. The solution of such buckling problem was carried out using both analytical and numerical methods. Axisymmetrical and asymmetrical plate buckling modes were analysed. Numerous results show the stability behaviour of composite plate with failures.